Identification guides for the most common genera of plant-parasitic nematodes - Eisenback, J. D. (Mactode Publications, 2015)
This set of full-colour guides is an invaluable resource for teaching the identification of the most common genera of plant parasitic nematodes. Each guide contains a high resolution light micrograph, a list of key features that are useful for the identification, a general distribution, the most common hosts, and a reference for two of the most recent and useful keys to species within the genus. The entire set contains 28 species of ectoparasites, migratory endoparasites, semi-endoparasites, and endoparasites. The collection of colour plates, suitable for framing, is contained in a notebook. In addition a set suitable for printing on a laser printer is included on a CD ROM. Purchase of the set includes permission to make a reasonable number of copies for teaching and other educational uses.